Are undocumented migrants' entitlements and barriers to healthcare a public health challenge for the European Union?. Issue 1 (December 2016) - De Vito, Elisabetta; de Waure, Chiara; Specchia, Maria; Parente, Paolo; Azzolini, Elena; Frisicale, Emanuela; Favale, Marcella; Teleman, Adele; Ricciardi, Walter
Abstract Undocumented migrants (UMs) are at higher risk for health problems because of their irregular status and the consequences of economic and social marginalization. Moreover, the emergent reality of undocumented migration in Europe calls for action in the field of management of UM's health demands as their access to health services has become a sensitive political and social issue. In this light, this paper aims to address UMs' entitlement and barriers to healthcare and related policies citing evidence from peer-reviewed and grey literature concerning people living in a country within the European Union without the legal right to be/remain in the destination country. A systematic review was performed using several databases and websites, and a total of 54 publications in English, with full text available, were taken into consideration. Between 2000 and 2015, Europe hosted the second largest number of international migrants (20 million, 1.3 million per year) after Asia. Even though there is limited evidence specifically focused on UMs' health, it is possible to state that infectious diseases, chronic illnesses, mental disorders, maternal-child conditions, dental issues, acute illnesses and injuries are the most common pathologies. In most cases across Europe, UMs have access only to emergency care. Even in countries where they are fully entitled to healthcare, formal and informal barriers hinder them from being or feeling entitled to this right. Socio-cultural barriers, such as language and communication problems, lack of formal and informal social and healthcare networks and lack of knowledge about the healthcare system and about informal networks of healthcare professionals are all common impediments. From the healthcare providers' perspective, there can be difficulties in providing appropriate care and in dealing with cultural and language barriers and false identification. Communication strategies play a central role in addressing the inequalities in access to healthcare services, and the definition and provision of specific training, focused on UMs' health needs, would be desirable. Improving access to healthcare for UMs is an urgent priority since the lack of access is proven to have serious consequences for UMs' health and wellbeing. Notwithstanding, few available examples of policies and best practices aimed at overcoming barriers in the delivery of healthcare to UMs are available.